Pematang Siantar in the Early Independence Period 1945-1947 - Suprayitno (Lakhomi Journal Scientific Journal of Culture, 2026)
This study examines the strategic role of Pematang Siantar during the early period of Indone-sian independence (1945–1947), when the city functioned as the administrative and military center of the Republic of Indonesia in Sumatra. Using a historical research method, the study employs heuristic, source criticism, interpretation, and historiographical approaches to analyze archival records, government documents, memoirs, and secondary historical sources. The findings reveal that the relocation of the Sumatra Provincial Government from Medan to Pematang Siantar in April 1946 was driven by the deteriorating security situation caused by Allied and Dutch (NICA) military operations. During approximately twenty months, Pema-tang Siantar became the center of governmental administration, military coordination, and logistical support for the Republican struggle, particularly in the Medan Area. The city also played a significant role in the reorganization of the Indonesian National Army (TNI), the establishment of the Regional Defense Council and the Regional Struggle Bureau, the issu-ance of the Province of Sumatra's Republican currency, and the consolidation of national uni-ty through visits by prominent leaders, including Vice President Mohammad Hatta. Despite internal challenges such as logistical shortages and tensions among military groups, Pematang Siantar remained a vital revolutionary city that strengthened the Republican government's resistance against Dutch military aggression. The study concludes that Pematang Siantar made a decisive contribution to sustaining the Republic of Indonesia in Sumatra by serving not only as a temporary capital but also as a strategic political, military, and economic center during one of the most critical phases of the Indonesian Revolution.